Methods for the strategic review of programmes for integrated management of childhood illness and community cases. (30th July 2018) - Dalglish, Sarah L
Abstract : Sarah Dalglish describes the purpose, methods, and process used to conduct the 2016 strategic review of Integrated Management of Childhood Illness and integrated Community Case Management